Transforming Tofu Waste into Healthy Chips: An Innovative Model of Economic Empowerment for Rural Communities - Faizatul Widat; Misuna; Fitri Nova Emilia; Nur Fadilatun Nisa (Communautaire: Journal of Community Service, 2024)
This research focuses on empowering the people of Sambirampak Kidul Village through the use of tofu waste into products of economic value, namely healthy chips. The purpose of this study is to develop and test an intervention model based on technical training and the use of simple technologies in waste management, as well as to measure the impact of the program on improving economic well-being and environmental management in the village. The research method used is a qualitative method with a case study approach, which allows researchers to deeply explore the experiences and views of the community towards this empowerment program. The data was collected through in-depth interviews, participatory observations, and document analysis, and then analyzed using thematic analysis techniques to identify the main patterns and themes that emerged from the data. The results of the study show that this program has succeeded in changing the community's perception of tofu waste from just waste to an economically valuable resource, as well as increasing income and environmental awareness in Sambirampak Kidul Village. The implication of this study is the importance of community-based education and empowerment in creating a sustainable and economically profitable waste management model. This research also makes a significant contribution to the development of community empowerment models that can be applied in various regions with similar conditions